The Moringa Superfood: Iconic Gastronomic Tourism Food in Ubud Gianyar: Makanan Super Kelor: Wisata Gastronomi yang Ikonik Makanan di Ubud Gianyar - Putu Sucita Yanthy; Yayu Indrawati; Azila Azmi; Ni Nyoman Sri Aryanti; L.G.L.K. Dewi; Ni Wayan Purnami Rusadi (Politeknik Pariwisata Makassar, Indonesia, 2024)
Moringa has gained popularity in the world of gastronomy due to its nutritional value and great versatility. Moringa leaves are rich in nutrients and can be used in a variety of dishes. The leaves have a unique flavor and a vibrant green color that enhances the dish. With such potential, moringa can become one of the most iconic gastronomic tourism foods, especially in Bali. This research aims to explore the potential of moringa as a gastronomic icon. The research utilizes a qualitative method by analyzing the results of in-depth interviews and interpreting the data. The research concludes that by understanding the uniqueness of moringa, this food ingredient can be developed into food and beverage menus that are widely consumable. Promotion through culinary festivals and events, moringa nutrition education, and incorporating moringa into cooking class activities are all efforts to establish this food ingredient as a gastronomic icon, particularly in Ubud, Gianyar. Furthermore, promoting moringa-based products can contribute to the promotion of health tourism, attracting visitors interested in wellness and nutritional benefits, thereby supporting the local economy.